Significance of Neuropilin-1 (CD 304) Expression in Paediatric B- Lineage Acute Lymphoblastic Leukemia (ALL) - Moizza Sahar, Fauzia Shafi Khan, Yusra Rashid, Farhana Shehzad, Ghulam Mustafa, Shahida Mohsin, Moizza Sahar, Fauzia Shafi Khan, Yusra Rashid, Farhana Shehzad, Ghulam Mustafa, Shahida Mohsin (Journal of Rawalpindi Medical College, 2019)
Background: To determine the prognostic significance of NRP-1 (CD304) expression in paediatric B-lineage Acute Lymphoblastic Leukaemia (ALL) patients. Methods: In this comparative study newly diagnosed cases (aged 1-15 years) of B-ALL were selected. Age and sex matched, 21 healthy controls were also included in the study to assess the NRP-1 expression on peripheral blood lymphocytes. A minimum 1ml of blood and bone marrow aspirate samples were taken in EDTA vacutainer and immunophenotyping was done on gated blast cells using an extensive panel of antibodies including myeloid markers (CD13, CD33 and cytoplasmic anti- MPO) and lymphoid markers (CD34, CD2, CD3, CD5, CD7, CD4, CD8, HLA DR, CD10, CD19, CD22; cytoplasmic CD3, CD22, CD79a and nuclear anti- TdT). The sample was considered NRP-1 positive if 20% or more of the gated blast cells expressed it . Man-Witney U test and Kruskal Wallis test were used for non-parametric data. The p value <0.05 was considered significant. Results: Out of 66 B-ALL patients, 53% were males. There were 20 (30%) NRP-1 positive and 46 (70%) NRP-1 negative patients. The prognosis of NRP-1 positive group was poor as compared to NRP-1 negative group with high blast percentage (80%) (p= 0.042), low morphological remission rate (21%) (p=0.004) and low survival rate (29%) (p=0.009). The mean survival days in dead patients was also less (22.75 days). Conclusion: NRP-1 over expression is associated with disease progression and severity in paediatric B-ALL patients.